Compass/BeiDou‐2 spaceborne clock performance assessment and its error detection, mitigation. Issue 4 (26th March 2015) - Chen, Maolin; Zhan, Xingqun; Du, Gang; Liu, Meihong
<x xml:space="preserve">Abstract</x> The performance of a spaceborne atomic clock on a navigation satellite and the accuracy of the clock data in broadcast ephemeris are two critical factors for real‐time high‐accuracy global navigation satellite systems applications. A novel clock performance assessment method is proposed, which is indexed by the maximum clock error, clock rate, and clock drift rate, and the performance of the BeiDou‐2 satellite‐borne clock is assessed by this method compared to the GPS. To mitigate the negative effects of clock errors on pseudo‐range measurements and positioning results, an integrated clock prediction method is also presented in this paper based on polynomial modeling, wavelet denoising, and autoregressive integrated moving average modeling. An example is shown to test and verify the effectiveness of the integrated clock prediction method. Real data clock assessment results demonstrate the equivalent quality of BeiDou‐2 and GPS spaceborne clocks. The proposed clock prediction method can be used to detect and mitigate clock errors in broadcast ephemeris. © 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.